Molecular characterization of large polycyclic aromatic hydrocarbons in solid petroleum pitch and coal tar pitch by high resolution MALDI ToF MS and insights from ion mobility separation. (December 2015) - Zhang, Wen; Andersson, Jan T.; Räder, Hans Joachim; Müllen, Klaus
Abstract: High resolution MALDI MS in combination with solvent free sample preparation was employed to characterize a petroleum pitch and a coal tar pitch. The elemental formulas of thousands of mass spectrometric peaks were assigned according to the accurate masses. Large polycyclic aromatic hydrocarbons (LPAHs) were found to be the major components in the complex mixtures. Iso-abundance plots were introduced to sort and visualize the molecular constituents into different types based on the carbon and double bond equivalence (DBE) numbers. The differences between the petroleum pitch and the coal tar pitch could be easily observed by comparing their iso-abundance plots. LPAHs in the investigated petroleum pitch possess broad carbon number and DBE number distributions and there is no significant change in the signal intensity between even and odd carbon numbered LPAH species. On the contrary, a smaller variety of carbon number and DBE number distribution of LPAH species is found in the investigated coal tar pitch and LPAHs with even carbon numbers are present in a significantly higher amount in comparison to the odd numbered species. Ion mobility mass spectrometry was used to differentiate the petroleum pitch from coal tar pitch and provides additional molecular size information of complex pitch samples.